2017
DOI: 10.3390/su9101729
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Association of Shrubs and Their Interrelation to Burrowing Site Preference of Subterranean Rodents on Dune Slope in the Otindag Sandy Land, China

Abstract: Rangelands worldwide have more shrubs now, and subterranean rangeland rodents show close interaction to shrubs when choosing a burrowing site. The study was conducted in Otindag Sandy Land in Inner Mongolia, China with the objective of determining the effects of slope position on spatial pattern and interaction of shrubs; how rodents choose their habitat in different slope; and shrubs and rodents influence each other. To accomplish the objective set, we used three physiographic units: Plot 1 (upper slope), Plo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…The univariate spatial autocorrelation and intraspecific spatial correlation of different age groups were analyzed at multiple scales by the pair-correlation function g (r) instead of the commonly used Ripley’s K-function in this study. The g-function, which is related to the derivative of the K-function, is more sensitive to small-scale effects in comparison with K-function [ 67 , 68 , 69 ]. The formula of function g (r) is as follows [ 39 , 70 ]: where A represents the plot area, n is the total plants number, and w ij means a weighting factor correcting for edge effects.…”
Section: Methodsmentioning
confidence: 99%
“…The univariate spatial autocorrelation and intraspecific spatial correlation of different age groups were analyzed at multiple scales by the pair-correlation function g (r) instead of the commonly used Ripley’s K-function in this study. The g-function, which is related to the derivative of the K-function, is more sensitive to small-scale effects in comparison with K-function [ 67 , 68 , 69 ]. The formula of function g (r) is as follows [ 39 , 70 ]: where A represents the plot area, n is the total plants number, and w ij means a weighting factor correcting for edge effects.…”
Section: Methodsmentioning
confidence: 99%
“…Grassland rodents, including voles, zokors, pikas, marmots, rabbits, and ground squirrels, play an important role in affecting ecosystem structure and function (Davidson et al., ; Jiang, Wang, Li, Shi, & Yang, ; Olofsson, Tømmervik, & Callaghan, ; Zhang, Zhong, & Fan, ). At moderate densities, rodents aid in maintaining diversity in the grassland, because their extensive excavations promote soil nutrient cycling and seed dispersal (Davidson et al., ); besides, they are a food resource to other animals in higher trophic levels (Delibesmateos, Smith, Slobodchikoff, & Swenson, ; Zhang, Zhang, & Liu, ).…”
Section: Introductionmentioning
confidence: 99%
“…Among the five recorded rodent species, the Apodemus peninsulaewas the most common in the Taihang Mountains, and the midslope and valley had more rodents than ridge. According to the 'landscape of fear' theory, vegetated habitats can provide shelter and improve survival chances for animals, so animals prefer vegetated habitats over open high-risk habitats (Laundre et al , 2001), small rodents were found in greater numbers in forested sparse grassland areas (Afonso, 2021), and nests around shrubs on the slopes could avoid the negative effects of rainfall and uphill runoff on burrows (Jiang et al , 2017). Furthermore, plants generally exhibit better growth in midslope compared to ridge and valley (Liao et al , 2021;Ohsawa & Ide, 2008), and the vertical structure of vegetation distribution on the mountain exhibits a central peak pattern (Lomolino, 2001).…”
Section: Rodent Abundancementioning
confidence: 99%